Transitory and permanent shocks in the global market for crude oil - Rebei, Nooman,Sbia, Rashid (International Monetary Fund, 2020)
This paper documents the determinants of real oil price in the global market based on SVAR model embedding transitory and permanent shocks on oil demand and supply as well as speculative disturbances. We find evidence of significant differences in the propagation mechanisms of transitory versus permanent shocks, pointing to the importance of disentangling their distinct effects. Permanent supply disruptions turn out to be a bigger factor in historical oil price movements during the most recent decades, while speculative shocks became less influential
10.5089/9781513528601.001
Keywords: Graue Literatur; Investments: Energy; Economic Theory; Industries: Energy; Energy: Demand and Supply; Energy and the Macroeconomy; Time-Series Models; Dynamic Quantile Regressions; Dynamic Treatment Effect Models; Diffusion Processes; State Space Models; Business Fluctuations; Cycles; Financial Institutions and Services: Government Policy and Regulation; Energy: General; Macroeconomics: Production; Agriculture: Aggregate Supply and Demand Analysis; Commodity Markets; Macroeconomics; Investment & securities; Petroleum; oil & gas industries; Economic theory & philosophy; Oil prices; Oil; Oil production; Supply shocks; Commodity price fluctuations; Commodities; Production; Economic theory; Prices; Petroleum industry and trade; Supply and demand; Oil market; Vector autoregressions; Narrative analysis; Bayesian estimation; Kalman filtering